Essentially-content aspects of personal data in the Republic of Belarus - Valiushka-Orsa, Natallia (Journal of the Belarusian State University. Law, 2019)
The article deals with the essentially-content aspects of personal data in the Republic of Belarus. Concrete proposals and recommendations have been made to improve the legal regulation of information relations in the field of personal data in our country. Based on the experience of foreign countries, the term «personal data» is interpreted. Hereby a proposal is made that it is advisable to include in the passport of a citizen of the Republic of Belarus a note on the blood group and blood rhesus. It is noted, that in modern conditions it is necessary to solve in many respects in a modern way issues related to the legal regulation of personal data in the Republic of Belarus. In general, the improvement of the national legislation in the field of personal data, including issues related to their protection, is very important for ensuring information security in the Republic of Belarus, which in turn creates real conditions for the further development of a unitary democratic social law-based state. A purposeful work on improving the legislation of all state bodies interested in this sphere will help improve the practice of its enforcement.